Model Manajemen Keuangan Keluarga Muslim Pada Perempuan Pekerja di Socah Dalam Prespektif Kesetaraan Gender Islam - Ahsaniya, Shynta Yuli; Endriyanti, Enni (Jurnal Iqtisaduna, 2023)
In managing family finances, women who work have greater opportunities, with good abilities women have a high influence in handling the family's economic conditions and the husband's trust in his wife influences the financial management of Muslim families and also has management principles in accordance with Islam which are beneficial for family both long and short term. Using the IFWM (Islamic family wealth management) design where families will live better is influenced by their expertise in designing and managing their respective finances. This research uses a qualitative method using a descriptive analysis approach. The research carried out by researchers aims to provide a significant solution in the form of providing a model of Muslim family financial management for working women in Socah from an Islamic gender equality perspective, so that working women throughout Indonesia have an idea of ​​how to manage Muslim family finances so that they do not make too many mistakes in management. Muslim family finances, especially for working women in Socah, Bangkalan district.